An Electrochemical Sensor Based on Reduced Graphene Oxide Modified Carbon Paste Electrode for Curcumin Determination in Human Blood Serum - Rahimnejad,Mostafa (2020)
A sensitive, accurate electrochemical sensor based on reduced graphene oxide modified carbon paste electrode (RGO/CPE) was developed to measure curcumin levels in human blood serum. The as-prepared electrode (RGO/CPE) was verified to outperform bare carbon paste electrode (CPE), with increased oxidation and reduction peaks at +0.505 V and +0.408 V, respectively. Curcumin measurement was performed using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. RGO/CPE showed a desirable linear response towards curcumin, within the concentration range of 10-6000 µM; the detection limit (S/N = 3) was 3.183 µM. Moreover, electrochemical impedance spectroscopy (EIS) and field emission scanning electron microscope (FESEM) were applied to gain further insight into the electrochemical behavior of the proposed electrode. The results revealed that the usage of RGO caused increased sensitivity of the sensor response to curcumin; therefore, RGO/CPE can be considered a promising electrochemical sensor for curcumin determination in human blood serum.